2020
DOI: 10.1002/brb3.1901
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consequences of infections by coronaviruses including severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)

Abstract: Background Anxiety and stress like mental illnesses are the common outcomes of viral epidemics and pandemics. Novel coronavirus disease 2019 (COVID‐19) outbreak caused by the severe acute respiratory syndrome coronavirus virus 2 (SARS‐CoV‐2) was first reported in Wuhan, China, and then spread all over the world in a short time. Objectives To highlight and discuss the impact of COVID‐19 pandemic on mental or psychological health. Method Literature search and collection of the information were performed using Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Facing public health emergencies, people experiencing stress responses are likely to encounter mental health problems [ 39 ]. The pandemic has increased the risk of psychological disorders, especially in confirmed cases of COVID-19 [ 40 ]. A meta-analysis about the prevalence of mental health problems in patients with COVID-19 showed prevalence rates of depression at 15.97%, anxiety at 15.5%, PTSD at 21.94%, and insomnia at 23.87% [ 41 ]—all far higher than usual [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Facing public health emergencies, people experiencing stress responses are likely to encounter mental health problems [ 39 ]. The pandemic has increased the risk of psychological disorders, especially in confirmed cases of COVID-19 [ 40 ]. A meta-analysis about the prevalence of mental health problems in patients with COVID-19 showed prevalence rates of depression at 15.97%, anxiety at 15.5%, PTSD at 21.94%, and insomnia at 23.87% [ 41 ]—all far higher than usual [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to protect newborns, a mother should limit the number of people they have contact with (44). Finally, other online strategies, such as online mental health services or telemedicine, can help alleviate the psychological problems of pregnant women by communicating with others remotely (51)(52)(53).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Furthermore, several studies have shown that the COVID-19 infection in association with infodemia increased the risk of psychiatric/psychological disorders by stimulating the hypothalamus–pituitary–adrenal (HPA) axis and has shown how dangerous this is for the public, especially for pregnant women and disabled people (Khan et al, 2020 , 2021 ; Nabi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%